1997
DOI: 10.1001/archinte.1997.00440310041004
|View full text |Cite
|
Sign up to set email alerts
|

The Use of D-Dimer Testing and Impedance Plethysmographic Examination in Patients With Clinical Indications of Deep Vein Thrombosis

Abstract: The results of the D-dimer assay and impedance plethysmographic examination on the day of presentation can be used to treat the majority of outpatients who present with clinical indications of deep vein thrombosis without further testing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
52
0
2

Year Published

1999
1999
2004
2004

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 110 publications
(59 citation statements)
references
References 21 publications
5
52
0
2
Order By: Relevance
“…Several studies have shown that this assay has a high negative predictive value and is a relatively sensitive but nonspecific marker for DVT. [1][2][3] Brotman et al evaluated the utility and limitations of D-dimer testing for evaluation of VTE in hospitalized patients. 4 Four different methods of D-dimer testing were used in this study.…”
Section: D-dimer Assaymentioning
confidence: 99%
“…Several studies have shown that this assay has a high negative predictive value and is a relatively sensitive but nonspecific marker for DVT. [1][2][3] Brotman et al evaluated the utility and limitations of D-dimer testing for evaluation of VTE in hospitalized patients. 4 Four different methods of D-dimer testing were used in this study.…”
Section: D-dimer Assaymentioning
confidence: 99%
“…More recently, both DVT and PE management studies have been performed, basing therapeutic decisions in part on D-dimer results. Ginsberg and colleagues 45 evaluated the results of a bedside wholeblood agglutination D-dimer assay and impedance plethysmography in patients with suspected DVT. When both studies were negative, anticoagulation was withheld and the patients monitored for three months.…”
Section: D-dimersmentioning
confidence: 99%
“…Ginsberg and colleagues [34] also recently evaluated the probability of DVT in patients by using D-dimer to limit the need for serial testing. They reported that among 273 patients who had a single normal result with IPG and a negative SimpliRED D-dimer result, 269 (98.5%; 95% CI, 96.3-99.6%) had no venous thromboembolic complications during the 3-month follow-up period.…”
Section: Diagnostic-testing Algorithmsmentioning
confidence: 99%